A Longitudinal Analysis of Site of Death: The Effects of Continuous Enrollment in Medicare Advantage Versus Conventional Medicare. (September 2017) - Chen, Elizabeth Edmiston; Miller, Edward Alan
This study assessed the odds of dying in hospital associated with enrollment in Medicare Advantage (M-A) versus conventional Medicare Fee-for-Service (M-FFS). Data were derived from the 2008 and 2010 waves of the Health and Retirement Study ( n = 1, 030). The sample consisted of elderly Medicare beneficiaries who died in 2008–2010 (34% died in hospital, and 66% died at home, in long-term senior care, a hospice facility, or other setting). Logistic regression estimated the odds of dying in hospital for those continuously enrolled in M-A from 2008 until death compared to those continuously enrolled in M-FFS and those switching between the two plans. Results indicate that decedents continuously enrolled in M-A had 43% lower odds of dying in hospital compared to those continuously enrolled in M-FFS. Financial incentives in M-A contracts may reduce the odds of dying in hospital.